Non-shivering thermogenesis is differentially regulated during the hibernation season in Arctic ground squirrels - Hunstiger, Moriah; Johannsen, Michelle Marie; Oliver, S. Ryan (Frontiers in Physiology, 2023)
Tissue from wild-caught Arctic ground squirrels were sampled over the course of nine months to assess the expression of proteins key to thermogenic regulation. Animals were sacrificed while aroused and extensor digitorum longus, diaphragm, brown adipose tissue, and white adipose tissue were probed using western blots to assess protein expression and blood was sampled for metabolite analysis. Significant seasonal expression patterns emerged showing differential regulation. Contrary to our prediction white adipose tissue showed no expression uncoupling protein 1 but utilization of uncoupling protein 1 appeared to peak in brown adipose tissue during the winter months but began to taper after terminal arousal in the spring. The opposite was true for muscular non-shivering thermogenesis. Sarco/endoplasmic reticulum calcium ATPase 1a and 2a expression was depressed during the late hibernation season and rebounded after terminal arousal in diaphragm tissue, but only SERCA2a was differentially expressed in extensor digitorum longus. Uncouplers sarcolipin was only detected in diaphragm samples and had decreased expression during hibernation. The differential timing of these non-shivering pathways would indicate distinct functions in maintaining thermogenesis depending on burrow temperature, availability of endogenous resources, and other seasonal activity demands on these tissues. These results could be impacted by fiber type make-up of the muscles collected, the body weight of the animal, and the date of entrance or exit from hibernation.